PERFORMATIVE ARCHIVES: EMBODYING MEMORY, ENVIRONMENT, AND SPIRIT IN INDIA’S INDIGENOUS KNOWLEDGE SYSTEMS - Vats, Nidhi (ShodhKosh: Journal of Visual and Performing Arts, 2026)
In India, indigenous knowledge systems are complicated epistemic worlds that are difficult to translate into textual archives or codified information. This paper suggests that this kind of knowledge is preserved through embodied practices: ritual healing, martial movement, artisanal labour, ecological stewardship, and spirit-mediated communication, which serve as living archives. It uses several examples in the region to show how memory, body, environment, and cosmology are set up to encode ecological intelligence, historical memory, and ethical relationships with both the land and community. The research criticizes the mainstream epistemologies that favour textuality and scientism and shows how the colonial and postcolonial paradigm splintered indigenous knowledge. This paper suggests a pluralistic, practice-oriented model of knowledge, taking into account bodily, sensory, and environmental aspects by foregrounding embodiment as an epistemic situation and not as a metaphor. The paper methodologically shifts from a text-based approach to one that focuses on bodily, sensory, and environmental experiences in creating and sharing knowledge. Embodiment is viewed as an actual way of knowing (epistemology) where a person’s memories, skills, and environmental awareness are combined. The approach encourages practitioners of indigenous knowledge to consider their practical methods as the main source of their knowledge systems and accepts these systems as valid epistemologies within contemporary India. It also illustrates how these "archives in motion" (memories, rituals, and the body performing) are not only epistemic sovereignty, but also provide valuable information for sustainable conservation, healthy policy, and a culturally sensitive environment.